STRUKTUR PENYAJIAN TARI GONG GAMAL SUKU DAYAK JAWANT KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Novita Anggraini Maharani; Ismunandar Ismunandar; Asfar Muniir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was motivated by the desire of researchers to find out the structure of the presentation of the Gong Gamal dance of the Dayak tribe in Jawant, Sekadau Hulu Subdistrict, Sekadau District. The purpose of this study is to describe the presentation structure that has its own characteristics both in terms of motion, music, rituals, and others. This research uses dance theory, presentation structure, dance presentation elements, and implementation of dance dance learning. The method used in this research is descriptive method with qualitative research. The approach used is a choreographic approach. The data contained in this study are facts regarding the structure of presentation of the Gong Gamal dance of the Jawant Dayak tribe, Sekadau Hulu Subdistrict, Sekadau District. Data were analyzed qualitatively, with resource persons Jaluni Domianus, Lukashitto, Onu Maria, and Itan Matheus who played active roles and found out about the Presentation Structure of Gong Gamal Dayak Jawant Tribe in Sekadau Hulu District, Sekadau District. The data is the result of observations, interviews, and documentation. Keywords: Structure Presentation, Dance Gong Gamal, Sekadau.